Fabrication of SiC-on-Insulator (SiCOI) Layers by Chemical Vapor Deposition of 3C-SiC on Si-in-Insulator Substrates at Low Deposition Temperatures of 1120 °C - Steiner, Johannes; Schultheiß, Jana; Wang, Shouzhong; Wellmann, Peter (Crystals, 2023)
Compared to bulk silicon carbide (SiC) wafers, SiC-on-insulator (SiCOI) substrates enable new device designs of electronic switches as well as novel photonic applications. One application is a micro-resonator for the usage in a Kerr frequency comb. For SiCOI substrates, a deposition temperature below 1200 °C is advisable due to stability reasons of the buried oxide layer during chemical vapor deposition (CVD) process conditions. To create 3C-SiC-on-insulator layers, a cold-wall CVD reactor was utilized, with propane and silane as the sources for carbon and silicon, respectively. To improve the cracking of the carbon source gas at low temperatures, the inner setup of the utilized cold-wall CVD reactor was changed to a non-water-cooled system. The change of the inner reactor setup was investigated numerically, and the grown epitaxial layers were characterized by Raman, EDX, SEM-imaging and XRD spectroscopy. We demonstrate successful deposition of 3C-SiC epitaxial layer substrates at temperatures below 1200 °C without delamination on SOI.
CRIS-Team Scopus Importer:2023-12-08
Keywords: chemical vapor deposition; COMSOL Multiphysics; cubic silicon carbide; photonic applications; silicon-on-insulator

Influence of the Size Distribution of the SiC Powder Source on the Shape of the Crystal Growth Interface during PVT Growth of 4H-SiC Boules - Schultheiß, Jana; Ihle, Jonas; Nanot, S. Usseglio; Bonanomi, S.; Munoz, D. Callejo; Hammer, R.; Wellmann, Peter (Trans Tech Publications Ltd, 2024)
We compared the evolution of three different SiC sources during standard PVT growth runs. The evolution of the growing crystal and the morphological changes in the SiC source were visualized using in-situ X-ray visualization. Computer simulation was used to calculate the temperature field distributions. It is found that the densification and shrinkage of the SiC source material during the growth process can affect the growth conditions in such a way that the convexity of the growth interface is increased in an unfavorable manner. While unfavorable growth conditions can be related to thermal properties due to less favorable SiC powder evolution, predicting such behavior is a rather complex task that still relies on the support of experimental methods.
CRIS-Team Scopus Importer:2025-02-04
Keywords: mass transport; SiC PVT growth; SiC source material; temperature field